Dynamic Analysis of the Growth of Building Area and the Immigrant Population in Shanghai based on the PVAR Model - Zhou, Zijing (Journal of Theory and Practice of Management Science, 2024)
Since the reform and opening up more than 30 years ago, Shanghai has witnessed rapid development of economic and continuous acceleration of urbanization and continuous growth of building area. However, the number of migrants has decreased over the same period, which is inconsistent with previous studies that show that population affects land demand and floor space. In this paper, panel data of each district of Shanghai from 2014 to 2018 are selected and the panel vector autoregression model (PVAR model) is constructed to analyze the dynamic relationship between the building area growth of each district of Shanghai, the immigrant population and the economic growth. The results show that : (a)There is no long‐term equilibrium relationship between the growth of Shanghai's floor area and the migration of foreign population. (b) The construction area growth in Shanghai can affect the regional GDP growth to a certain extent. (c) The migration of migrants into Shanghai has a certain effect on the economic growth of Shanghai.